Determination of the Excitatory Effects of MicroRNA-30 in the Self-Renewal and Differentiation Process of Neonatal Mouse Spermatogonial Stem Cells: - Hedayatpour, Azim; Khanehzad, Maryam; Abolhasani, Farid; Hassanzadeh, Gholamreza; Nourashrafeddin, Seyed Mehdi (Galen Medical Journal, 2020)
Background: Spermatogonial stem cells (SSCs) are considered as special stem cells since they have the ability of self-renewal, differentiation, and transferring genetic information to the next generation. Also, they considered as vital players in initiating and preserving spermatogenesis. The fate decisions of SSCs are mediated by intrinsic and extrinsic factors, among which microRNAs (miRNAs) are one of the most essential factors in spermatogenesis among endogenous regulators. However, the mechanisms by which individual miRNAs regulate self-renewal and differentiation of SSCs are unclear. The present study aimed to evaluate the impact of miRNA-30 mimic on fate determinations of SSCs. Materials and Methods: The obtained SSCs from neonatal mice (3-6 days old) were purified by MACS and flow cytometry with a promyelocytic leukemia zinc-finger marker. Then, the cultured cells were transfected with miRNA- 30 mimic, and finally, the changes in expressing ID4 and c-kit proteins were assessed by western blot analysis. Results: According to flow cytometry findings, the percentage of SSC purity was about 98.32. The expression of ID4 protein and colonization increased significantly through the transfection of miRNA-30 mimic (P<0.05). Conclusion: The miRNA-30 controls spermatogonial stem cell self-renewal and differentiation, which may have significant implications for treating male infertility. [GMJ.2020;9:e1829]